Estimation of TV Tubes Acceptance Inspection Functioning Efficiency - Vaišvila, A.; Kalnius, R.; Eidukas, D. (Elektronika ir Elektrotechnika, 2005)
There is analyzed 2-stage selective acceptance inspection according to two parameter groups, when condemned as rejected groups of products are completely checked and product flows with fixed defection level are inspected. Estimation models of acceptance inspection efficiency were created. There were analyzed seven real joint plan variants of acceptance (the first stage) and inspective (the second stage) control according to different groups. There was estimated the dependence of recurrent flows on parameters of inspection plans and the totality of accepted groups of products (ready production in storage) defection level variation, in relation with production flow defection level and repeated inspection operation second rate error probability during product classification. There are presented numeral realizations with conclusions and recommendations. Ill.4, bibl. 10 (English, summaries in Lithuanian, English and Russian).